Effect of a diet and exercise intervention on oxidative stress, inflammation and monocyte adhesion in diabetic men - Roberts, Christian K.; Won, Dean; Pruthi, Sandeep; Lin, San San; Barnard, R. James (Diabetes research and clinical practice, 2006)
Diabetes increases the risk of coronary artery disease. We examined the effects of lifestyle modification on key contributing factors to atherogenesis, including oxidative stress, inflammation and cell adhesion. Diabetic men ( N = 13) were placed on a high-fiber, low-fat diet in a 3-week residential program where food was provided ad libitum and daily aerobic exercise was performed. In each subject, pre- and post-intervention fasting blood was drawn for circulating levels of serum lipids, glucose and insulin, oxidative stress marker 8-isoprostaglandin F 2α (8-iso-PGF 2α), the inflammatory protein C-reactive protein (CRP), and soluble intracellular adhesion molecule (sICAM)-1 and sE-selectin as indicators of endothelial activation. Using subject sera and human aortic endothelial cell (HAEC) culture systems, serum-induced monocyte adhesion, ICAM-1, vascular cell adhesion molecule-1 (VCAM-1) and cell surface abundance, and monocyte chemotactic protein-1 (MCP-1) production were determined. Nitric oxide (NO), superoxide, and hydrogen peroxide production were measured in vitro by fluorometric detection. After 3 weeks, significant reductions ( p < 0.05) in BMI, all serum lipids including total cholesterol (pre: 188.9 ± 10.1 mg/dL versus post: 146.3 ± 3.8 mg/dL) and low-density lipoprotein (103.1 ± 10.2 mg/dL versus 76.4 ± 4.3 mg/dL), fasting serum glucose (157.5 ± 10.1 mg/dL versus 126.7 ± 8.7 mg/dL), insulin (33.8 ± 4.0 μU/ml versus 23.8 ± 3.4 μU/ml), homeostasis model assessment for insulin resistance, 8-iso-PGF 2α, CRP, sICAM-1, and sE-selectin were noted. In vitro, serum-stimulated monocyte adhesion, cellular ICAM-1 and VCAM-1 expression ( p < 0.05), and fluorometric detection of superoxide and hydrogen peroxide production decreased, while a concomitant increase in NO production was noted (all p < 0.01). A combination of diet and exercise ameliorates oxidative stress, inflammation, and monocyte-endothelial interaction. Intensive lifestyle modification may improve novel CAD risk factors in men with diabetes.